Simultaneous Transfer of Leaf Rust and Powdery Mildew Resistance Genes from Hexaploid Triticale Cultivar Sorento into Bread Wheat - Li, Feng; Li, Yinghui; Cao, Lirong; Liu, Peiyuan; Geng, Miaomiao; Zhang, Qiang; Qiu, Lina; Sun, Qixin; Xie, Chaojie (Frontiers in Plant Science, 2018)
Wheat powdery mildew, caused by Blumeria graminis f. sp. tritici, and wheat leaf rust, caused by Puccinia triticina Eriks, are two important diseases that severely threaten wheat production. Sorento, a hexaploid triticale cultivar from Poland, shows high resistance to the wheat powdery mildew isolate E09 and the leaf rust isolate PHT in Beijing, China. To introduce resistance genes into common wheat, Sorento was crossed with wheat line Xuezao, which is susceptible to both diseases, and the F1 hybrids were then backcrossed with Xuezao as the recurrent male parent. By marker analysis, we demonstrate that the long arm of the 2R (2RL) chromosome confers resistance to both the leaf rust and powdery mildew isolates at adult-plant and seedling stages, while the long arm of 4R (4RL) confers resistance only to powdery mildew at both stages. The chromosomal composition of BC2F3 plants containing 2R or 2RL and 4R or 4RL in the form of substitution and translocation were confirmed by GISH (genomic in situ hybridization) and FISH (fluorescence in situ hybridization). Monosomic and disomic substitutions of a wheat chromosome with chromosome 2R or 4R, as well as one 4RS-4DL/4DS-4RL reciprocal translocation homozigote and one 2RL-1DL translocation hemizigote, were recovered. Such germplasms are of great value in wheat improvement.